Methacrylic Zwitterionic, Thermoresponsive, and Hydrophilic (Co)Polymers via Cu(0)‐Polymerization: The Importance of Halide Salt Additives. Issue 4 (22nd December 2015) - Simula, Alexandre; Anastasaki, Athina; Haddleton, David M.
Abstract : The synthesis of hydrophilic, thermoresponsive, and zwitterionic polymethacrylates is reported by Cu(0)‐mediated reversible deactivation radical polymerization in water and/or water/alcohol mixtures. The predisproportionation of [Cu I (PMDETA)Cl] in water prior to initiator and monomer addition is exploited to yield well‐defined polymethacrylates with full monomer conversions in 30 min. The addition of supplementary halide salts (NaCl) enables the synthesis of various molecular weight poly[poly(ethylene glycol) methyl ether methacrylate] (PEGMA475 ) ( DP n = 10–80, M n ≈ 10 000–40 000 g mol −1 ) with full monomer conversion and narrow molecular weight distributions attained in all cases ( Đ ≈ 1.20–1.30). A bifunctional PEG initiator (average M n ≈ 1000 g mol −1 ) is utilized for the polymerization of a wide range of methacrylates including 2‐dimethylaminoethyl methacrylate, 2‐morpholinoethyl methacrylate, [2‐(methacryloyloxy)ethyl]dimethyl‐(3‐sulfopropyl)ammonium hydroxide, and 2‐methacryloyloxyethyl phosphorylcholine. Despite the high water content, high end group fidelity is demonstrated by in situ chain extensions and block copolymerizations with PEGMA475 yielding well‐defined functional telechelic pentablock copolymers within 2.5 h. Abstract : The synthesis of zwitterionic, hydrophilic, and thermoresponsive polymethacrylates is reported by Cu(0)‐mediated polymerization in aqueous media. Copolymerization of 2‐dimethylaminoethyl methacrylate, 2‐morpholinoethyl methacrylate, [2‐(methacryloyloxy)ethyl]dimethyl‐(3‐sulfopropyl)ammonium hydroxide, and 2‐methacryloyloxyethyl phosphorylcholine with poly(ethylene glycol) methyl ether methacrylate is reported with near quantitative monomer conversion and moderate molecular weight distribution attained ( Đ < 1.5).